Corpora amylacea in prostatectomy tissue and associations with molecular, histological, and lifestyle factors. Issue 15 (15th July 2018) - DuPre, Natalie C.; Flavin, Richard; Sfanos, Karen S.; Unger, Robert H.; To, Samantha; Gazeeva, Elizaveta; Fiorentino, Michelangelo; De Marzo, Angelo M.; Rider, Jennifer R.; Mucci, Lorelei A.
Abstract : Background: Corpora amylacea are amyloid bodies commonly found adjacent to damaged prostate epithelium. Little is known about their formation or function. The current study sought to characterize corpora amylacea in prostate tissue and to describe their relationship with clinical, histological, molecular, and lifestyle factors, especially with chronic inflammation which is associated with aggressive disease. Methods: We studied a cohort of 355 men with prostate cancer and tissue specimens from the Health Professionals Follow‐Up Study. Pathologists examined H&E slides and undertook a standardized review for histologic data and inflammation. Trained observers counted corpora amylacea within the benign and predominately tumor areas. Immunohistochemistry biomarkers were available from tissue microarrays. We used multivariable logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI) to assess associations of chronic inflammation, clinical, histological, molecular, and lifestyle factors with the presence of corpora amylacea. Results: Corpora amylacea were present in benign tissue area for 298 men (84%). Specimens with moderate‐to‐severe chronic inflammation were more likely to have corpora amylacea in benign regions (OR = 5.4 95%CI 1.9, 15.6). Moreover, corpora amylacea were more common in men with higher body mass index (OR = 1.13 95%CI 1.01, 1.26). In contrast, Gleason grade (OR = 0.4 95%CI 0.2, 0.8), proliferation index (OR = 0.6 95%CI 0.3, 1.2) and the presence of the TMPRSS2:ERG fusion (OR = 0.4 95%CI 0.2, 0.8) were inversely associated with corpora amylacea presence. TURP specimens were less likely to have corpora amylacea than prostatectomy specimens (OR = 0.12 95%CI 0.03, 0.47). Age, PSA, stage, biomarkers of angiogenesis and PTEN, and vasectomy were not significantly associated with corpora amylacea. Conclusion: Corpora amylacea were common among men with prostate cancer and were associated with pro‐inflammatory factors, some markers of less aggressive disease, and lack of the TMPRSS2:ERG fusion.